Overview of Patient Boarding Time At the Emergency Installation of Toto Kabila Hospital - Rey Afriansyah Gobel; Zuhriana K. Yusuf; Moh. Nisyar Sy Abd. Azis (Universitas Muhammadiyah Palu, 2026)
Boarding time is an important indicator of the quality of emergency room services that describes the length of time from the time the patient is designated for hospitalization until he is transferred to the treatment room. Prolonged boarding time can lead to delays in further treatment, increase the risk of complications, and impact patient safety. This study aims to find out the description of the boarding time of patients in the Emergency Installation of Toto Kabila Hospital. The research design is descriptive quantitative with a single variable boarding time. The population amounted to 1132 emergency room patients, with a sample of 92 respondents using purposive sampling techniques. Data were collected through direct observation and verification of medical records, then analyzed in univariate analysis. The results of the study showed that 53 respondents (57.6%) experienced boarding time ? 6 hours, while 39 respondents (42.4%) experienced boarding time > 6 hours. The main cause of boarding time is the limited number of beds in the inpatient room. Other contributing causes are extra work of nurses, administration and documentation and patient or family factors. These findings show that patient transfers have gone quite well, although some patients are still experiencing delays. Toto Kabila Hospital is recommended to improve boarding time monitoring and improve the bed availability information system. Further research is suggested to develop other variables to gain a more comprehensive understanding of boarding time.